The Theory of Hedging and Speculation in Commodity Futures - Johnson, Leland L. (Review of Economic Studies, 1960)
The Theory of Hedging and Speculation in Commodity Futures Get access Leland L. Johnson Leland L. Johnson Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 3, June 1960, Pages 139–151, https://doi.org/10.2307/2296076 Published: 01 June 1960